Empowering the Implementation of Self-Regulated Learning Through Project-Based Learning (PjBL) in English Instruction - Sukmawati; Rosmayanti, Vivit; Amin, Sulvahrul; Sujarwo; Akhiruddin; Christo, Yudi; Khatima, Chusnul (Jurnal Pendidikan dan Pengajaran, 2025)
Students accustomed to more teacher-centered methods may find it challenging to take the initiative, create goals, and monitor their learning required by SRL. In addition to covering the essential material, teachers must create projects that promote SRL. This study aimed to test the effect of project-based Learning (PjBL) on empowering students’ self-regulated learning in some schools in South Sulawesi. The current study utilized a descriptive-quantitative methodology with structural equation modelling (SEM) and partial least squares (PLS) statistical analysis. The population of each school is 1.120 students. This study applied random purposive sampling, and the number of samples was 285 students. Findings show that the structural model reflected the relationship between variables and tested the hypothesis in the inner model. The results described that implementation of project-based learning is effective on student’s self-regulated learning is proved by a t-test of 38.745 smaller than the t-table of 1.96 and the p-value is smaller than 0.05 (p-value =0.00) so it can be seen that all indicators on self-regulated learning have a positive influence on the implementation of project-based learning (PjBL) model. It can be concluded that the key determinant that has the most substantial influence on the quality of students is the effective delivery of project-based learning in fostering the development of self-regulated learning. The implication requires professional development to effectively integrate PjBL with SRL strategies. Training could focus on designing projects that promote self-regulation and developing assessment methods of students' SRL skills.